Primary malignant melanoma of the lung: a case report of a rare tumor and review of the literature. Issue 1 (2nd January 2018) - Yunce, Muharrem; Selinger, Stephen; Krimsky, William; Harley, Daniel P.
ABSTRACT: Primary malignant melanoma of the lung (PMML) is a rare malignancy that exhibits aggressive behavior and has a very poor prognosis. We are reporting on a case of PMML in an otherwise healthy 22-year-old Caucasian male with no significant past medical history and an unremarkable family history. The patient initially presented with a 2-month history of a cough and an unexplained 22-lb weight loss. His initial chest X-ray demonstrated opacification of the right lower lobe (RLL) of his lung and a subsequent computerized tomography scan (CT scan) of his lung revealed a large mass occupying most of his RLL (Figure 1). The patient subsequently underwent a bronchoscopy with endobronchial ultrasound. Biopsies revealed a poorly differentiated carcinoma. A positron emission tomography with low dose CT scan was performed per protocol and revealed an intensely hypermetabolic tumor with no evidence for lymphatic disease or extra-thoracic spread. The patient underwent a surgical exploration and a right lower lobectomy with a thoracic lymphadenectomy. The pathology including immunohistochemical stains demonstrated a malignant melanoma with no lymph node involvement. A physical examination including ophthalmic, mucosal, and skin examinations revealed no evidence for an extra-thoracic site of the disease. The patient had negative margins for resection and did not receive any adjuvant therapy and is alive and well with no evidence for recurrence 3 years after the resection.